The Legal and Regulatory Framework for Microfinance in Iraq - Abdel Aziz, Teymour; Abbassi, Alaa; Chehade, Nadine; Lauer, Kate (World Bank, Washington, DC, 2016)
A well-functioning and inclusive financial sector is critical for efficient resource allocation leading to increased productivity, greater investment, higher overall levels of economic growth, and lower inequality. This is particularly critical in Iraq, where years of political instability and violence have impeded the development of a robust private sector. Microfinance services in Iraq are still nascent and far from meeting their full potential. This diagnostic report aims to present the microfinance landscape in Iraq, its legal and regulatory framework, and potential policy improvements to enhance the operating environment. It aims to inform public and private sector stakeholders on the regulations and laws affecting the development and strategic direction of the microfinance sector. The policy recommendations presented are designed to address factors preventing greater growth and outreach, with the goal of promoting inclusive financial sector development in Iraq.